Faktor–Faktor yang Mempengaruhi Tingkat Kepuasan Anggota Pengguna Jasa Koperasi Simpan Pinjam Artha Niaga Sentosa Surabaya - Moh Muklis Sulaeman; Ruswaji Ruswaji; Puguh Cahyono (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this study is 1) To determine the factors that influence the level of satisfaction of members using the services of the Artha Niaga Sentosa Savings and Loan Cooperative. The approach in this study uses explanatory research with a survey method (Survey Method) with a simple random sampling technique of 109 respondents. Data collection techniques are questionnaires, interviews, surveys and documentaries. while the data taken are primary data and secondary data, while the data analysis technique using multiple linear regression. The results showed that: 1) Service quality had no effect on member satisfaction, which was proven by a significance value of 0.858 > 0.05. 2) trust has no effect on member satisfaction as evidenced by a significance value of 0.121 > 0.05 3) brand image has a significant effect on member satisfaction as evidenced by a significance value of 0.047 < 0.05. Of the three independent variables, brand image gives the most dominant contribution to the satisfaction of members using the services of the Artha Niaga Sentosa Savings and Loan Cooperative.